NEUROMODULATION IN ANXIETY AND DEPRESSIVE DISORDERS: MECHANISMS OF ACTION, EFFICACY, AND DIRECTIONS FOR PERSONALIZED THERAPY - Jakub Przerwa (International Journal of Innovative Technologies in Social Science, 2025)
The aim of this article is to present current research and conclusions regarding the effectiveness, mechanisms of action, and clinical applications of neuromodulation methods-such as transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), transcranial alternating current stimulation (tACS), transcranial random noise stimulation (tRNS), and noisy galvanic vestibular stimulation (nGVS)-in the treatment of depressive and anxiety disorders, with particular emphasis on their neurobiological foundations.Neuromodulation represents a novel, promising therapeutic strategy in the treatment of affective and anxiety disorders, especially in patients resistant to pharmacotherapy and psychotherapy. Techniques using electrical and electromagnetic modulation have demonstrated antidepressant effects that may constitute an important component of the therapeutic approach in these disorders. Transcranial magnetic stimulation and transcranial direct current stimulation influence prefrontal–limbic circuits, normalizing functional connectivity through the regulation of cortical excitability and activation of signaling pathways involving brain-derived neurotrophic factor (BDNF). More recent techniques such as tACS and tRNS enable frequency-specific modulation of neuronal oscillations, showing promising results in treatment-resistant depression. The routine use of neuromodulation in depressive and anxiety disorders-particularly when other treatments have proven ineffective-may become a new therapeutic paradigm in psychiatry. However, further clinical studies are required to standardize stimulation parameters and assess the long-term efficacy of these methods.